A rare case of primary tuberculosis of female genital tract - Kamarudin, Norhidayah; Abdul Samat, Muttaqillah Najihan; Zainol Rashid, Zetti (2018)
Female genital tract tuberculosis (FGTB) is frequently considered as secondary TB which originates from other primary lesions or as a complication of an extrapulmonary TB. Primary FGTB is seldom reported and often unrecognized due to the nature of the disease that masquerade other gynaecological conditions with considerable proportion of patients are asymptomatic (Grace 2017). Causal relationship of FGTB with female infertility is well established, and the condition is typically diagnosed during evaluation for the cause of infertility (Namavar et. al. 2001). We report a potential case of symptomatic primary FGTB and emphasize on the combination of diagnostic modalities useful for diagnosis.